Dignity in cancer patients with a life expectancy of a few weeks. Implementation of the factor structure of the Patient Dignity Inventory and dignity assessment for a patient-centered clinical intervention: A cross-sectional study. Issue 6 (7th February 2018) - Bovero, Andrea; Sedghi, Nader Alessandro; Botto, Rossana; Tosi, Chiara; Ieraci, Valentina; Torta, Riccardo
Abstract: Objective: Hospice is a favored setting for dignity care. Studies on dignity dimension in end-of-life patients are growing. The Patient Dignity Inventory (PDI) is a tool that can lead to interesting information on dignity-related aspects of suffering. The study aimed to investigate dignity among end-of-life cancer patients, by examining the Italian version of the PDI factor structure and assessing the relationship between dignity and other patients' psychosocial and spiritual variables to improve a patient-centered clinical practice. Method: This is a cross-sectional study. Data were collected using a battery of self-administered validated rating scales. The sample included 127 hospice patients with a life expectancy of a few weeks and a Karnofsky Performance Status ≤40. Factor structure and concurrent validity of PDI and correlations between dignity and anxious and depressive symptomatology, quality of life, demoralization, personal coping styles, spiritual well-being, and spiritual daily experience were analyzed. Result: Factor analysis highlighted a five-factor solution, accounting for 60% of the overall variance. The factors were labeled Psychological Distress, Social Support, Physical Symptoms and Dependency, Existential Distress, and Loss of Purpose/Meaning. Dignity assessment evidenced that self-blame coping style, emotional and physical well-being, and depression were the loss of dignity significant predictors ( R 2 = 0.605; p < 0.01). Significance of results: The results point out the intercultural validity of the PDI and empower an accurate detection of dignity-related distress sources in the daily clinical practice. Personality traits seem to have an active role in the loss of dignity, whereas spirituality is confirmed to be positively involved in dignity enhancement.